Study of lamination quality of solar modules with PMMA front layer. Issue 3 (1st July 2019) - Drabczyk, Kazimierz; Sobik, Piotr; Starowicz, Zbigniew; Gawlińska, Katarzyna; Pluta, Anna; Drabczyk, Bogusław
Abstract : Purpose: The photovoltaic modules with front glass as a protective layer are the most popular type in the industry, but for some applications it can be considered as too heavy. One of the approaches is to laminate the cells using PMMA [Poly(methyl methacrylate)] as the front layer. This polymer has good mechanical strength and optical properties but exhibits low adhesion to lamination foil. To increase adhesion between these two materials, PMMA surface treatment may be required. Design/methodology/approach: To examine the PMMA treatment influence on the sample, adhesion samples' surfaces were modified by grinding and laser cutting. Also two types of PMMA available in the market were tested, namely, smooth and satin types. The quality of lamination was determined using two methods, namely, tear test with recorded maximal tear force achieved for the samples, and environment chamber tests, in which the system resistance against the cyclic temperature variation was evaluated. Findings: Additional treatment of the PMMA surface lead to increased adhesion of the lamination foil used. Ethylene-vinyl acetate foil in the PMMA system is sensitive to temperature variation, which can lead to system delamination, whereas polyvinyl butyral foil exhibits better environmental performance and even its adhesion to PMMA is lower. Originality/value: This paper presents atypical surface modification methods that contributed to higher adhesion of lamination systems in glass-free solar modules. Glass front sheet and polymeric backsheet were replaced with PMMA. As the adhesion mechanism in the PMMA-lamination foil system differs from that in the traditional glass system, different PMMA surface treatments need to be evaluated.